Reverse osmosis a guide for the nonengineering professional - Spellman, Frank R. (CRC Press, Taylor and Francis Group, 2016)
This book describes all of the basic processes involved in reverse osmosis operations. Presented in a conversational style-using jargon-free language-it discusses in detail the drinking water purification, wastewater reuse, desalination processes, and other freshwater applications used to ensure the safe consumption of water.